Examining the Use of Sodium Nitroprusside in Coronary Artery Bypass Grafting: Is the Benefit Worth the Cost?. Issue 7 (July 2017) - Gibson, Caitlin M.; Davis, Sondra; Bradford, Darien
Purpose: Sodium nitroprusside is a vasodilator frequently used in the coronary artery bypass grafting (CABG) setting. However, the price of a 50-mg vial of sodium nitroprusside increased from $5.00 in 2003 to up to $900 in 2016. The purpose of this review is to help health systems balance high-quality patient care with economic responsibility.Methods: A MEDLINE literature search was performed using the search terms "nitroprusside" and "coronary artery bypass." All English-language trials in human subjects assessing the use of sodium nitroprusside in the setting of CABG were evaluated. The references of these studies were also reviewed.Results: In the setting of CABG, sodium nitroprusside attenuates conduit vasospasm and reduces the incidence of inflammation, atrial fibrillation, and acute kidney injury after surgery. However, other vasodilators are more effective at maintaining postoperative blood pressure at goal.Conclusions: Despite its cost, sodium nitroprusside may be an appropriate agent to use during CABG operations, but other agents should be considered for treatment of postoperative hypertension.